Diversity of Pectin Rhamnogalacturonan I Rhamnosyltransferases in Glycosyltransferase Family 106 - Wachananawat, Bussarin; Kuroha, Takeshi; Takenaka, Yuto; Kajiura, Hiroyuki; Naramoto, Satoshi; Yokoyama, Ryusuke; Ishizaki, Kimitsune; Nishitani, Kazuhiko; Ishimizu, Takeshi (Frontiers in Plant Science, 2020)
Rhamnogalacturoan I (RG-I) comprises approximately one quarter of the pectin molecule in land plants, and the backbone of RG-I consists of a repeating sequence of [2)-alpha-L-Rha(1-4)-alpha-D-GalUA(1-] disaccharide. Four Arabidopsis thaliana genes encoding RG-I rhamnosyltransferases (AtRRT1 to AtRRT4), which synthesize the disaccharide repeats, have been identified in the glycosyltransferase family (GT) 106 family. However, the functional role of RG-I in plant cell walls and the evolutional history of RRTs remains to be clarified. Here, we characterized the sole ortholog of AtRRT1–AtRRT4 in liverwort, Marchantia polymorpha, namely MpRRT1. MpRRT1 had RRT activity and genetically complemented the AtRRT1-deficient mutant phenotype in Arabidopsis. However, the MpRRT1-deficient M. polymorpha mutants showed no prominent morphological changes and only an approximate 20% reduction in rhamnose content in the cell wall fraction compared to that in wild-type plants, suggesting the existence of other RRT gene(s) in the M. polymorpha genome. As expected, we detected RRT activities in other GT106 family proteins such as those encoded by MpRRT3 in M. polymorpha and FRB1/AtRRT8 in A. thaliana, the deficient mutant of which affects cell adhesion. Our results show that RRT genes are more redundant and diverse in GT106 than previously thought.